Investigating The Determinant Factors of E-Mas Saving Decisions on Indonesian Sharia Bank Customers: AIDA Model Development - Afandi, Ahmad; Siregar, Try Mahendra; Nikmah, Faridhatun (MALIA: Journal of Islamic Banking and Finance, 2024)
The popular feature of BSI mobile presently is the e-Mas, considered a modern investment choice for society. This research aims to investigate the decisive factors influencing BSI Mobile e-Mas savings decisions. AIDA modeling was enhanced by incorporating the notions of knowledge and motivation into the investigation. We gathered data from 240 customers through individual questionnaire completion. The Partial Least Square structural equation model (PLS-SEM) was utilized to analyze the data using AMOS version 24.0. The results indicate that the AIDA model (Attention, Interest, Desire, Action), knowledge, and motivation have a positive impact on saving decisions. BSI Mobile e-Mas Savings is a new service that lacks assurance from the Deposit Insurance Corporation, hence requiring prompt legislative rules from the government and banks